2012
DOI: 10.1259/bjr/74041910
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of thin-slice (1 mm) axial proton density MR images for identification and classification of meniscal tears: correlative study with arthroscopy

Abstract: Objective: To evaluate the diagnostic efficacy of thin-slice (1 mm) axial proton density-weighted (PDW) MRI of the knee for meniscal tear detection and classification. Methods: We prospectively assessed pre-operative MR images of 58 patients (41 males, 17 females; age range 18-62 years) with arthroscopically confirmed meniscal tear. First, we evaluated the performance of the sagittal and thin-slice axial MR images for the diagnosis of meniscal tears. Second, we compared the correlation of tear types presumed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…For sagittal PD WIs, the sensitivity was 90.62% and specificity 70.73% for the medial meniscal tears while for the lateral meniscus the sensitivity was 72.73% and specificity 77.1%. For axial images, the sensitivity was 97.3% for the medial meniscal tears and 84% specificity while for the lateral meniscal tears sensitivity was 95.65% and specificity 80.56% [11].…”
Section: Discussionmentioning
confidence: 92%
“…For sagittal PD WIs, the sensitivity was 90.62% and specificity 70.73% for the medial meniscal tears while for the lateral meniscus the sensitivity was 72.73% and specificity 77.1%. For axial images, the sensitivity was 97.3% for the medial meniscal tears and 84% specificity while for the lateral meniscal tears sensitivity was 95.65% and specificity 80.56% [11].…”
Section: Discussionmentioning
confidence: 92%
“…This has been shown to provide increased sensitivity and specificity regarding the diagnosis and classification of meniscal tears of the knee and likewise may prove effective for the management of OLT. 22 Additionally, recent developments in 3D MRI sequences with slice thicknesses of 0.5 mm have provided a novel modality for highly accurate 3D reconstructions, comparable to CT, while offering superior resolution of articular cartilage and its attachment to the underlying subchondral bone. 23-25 However, the use of thin-sliced 3D MRI for evaluation of OLT, specifically, has yet to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…8 In 2011, a study by G. Gokalp et al on the contribution of thin-slice(1 mm) axial proton density MR images for the identification and classification of meniscal tears in correlation with arthroscopy, showed that thinner sections can better reveal the signal-surface contact and tear morphology. 9 Yoon et al 10 performed TSE PDW MRI with 1mm thickness and observed inadequate tissue contrast because of the presence of a certain degree of image degradation during the multi-planar reconstruction process owing to nonisotropic images.…”
Section: )mentioning
confidence: 99%
“…But the advantage of axial imaging for the assessment of vertical and vertical-horizontal tears are to be considered as, clinically the horizontal tears are usually not easily repairable while longitudinal tears are often repairable and radial tears may be repairable depending on its location. 9 In our study, we are assessing the value of axial MR reconstructed images, alone and in combination with other imaging planes, for the diagnosis of meniscal tears of the knees, keeping arthroscopy as the gold standard for the diagnosis of the same.…”
mentioning
confidence: 99%